2022
DOI: 10.1111/1346-8138.16582
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐specific immunotherapy induces monocyte‐derived dendritic cells but attenuates their maturation and cytokine production in the lesional skin of an atopic dermatitis mouse model

Abstract: Atopic dermatitis (AD) is a common inflammatory skin disease, but current treatments for AD are mostly limited to the alleviation of symptoms and inhibition of inflammation. Allergen‐specific immunotherapy (ASIT) is the only curative approach for allergic diseases and could be a promising way to cure AD. Although ASIT has been gradually applied to patients with AD, there are still few studies on its efficacy evaluation and mechanisms. Based on our previous established AD mouse model by dinitrofluorobenzene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…[48][49][50] Activated B cells have been observed to secrete various cytokines, including IL-6, IFN-γ, TNF-α, and IL-10. [51,52] In contrast, CD4 + T cells that have been activated characterized by deposition of ICs. [53][54][55] Additionally, research conducted on NZB/NZW lupus mice revealed a rise in BAFF during the initial phase of SLE, and the concentration of BAFF in the serum was directly correlated with the extent of renal damage.…”
Section: Type Of Disease Antigen Diagnostic/prognostic Value Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] Activated B cells have been observed to secrete various cytokines, including IL-6, IFN-γ, TNF-α, and IL-10. [51,52] In contrast, CD4 + T cells that have been activated characterized by deposition of ICs. [53][54][55] Additionally, research conducted on NZB/NZW lupus mice revealed a rise in BAFF during the initial phase of SLE, and the concentration of BAFF in the serum was directly correlated with the extent of renal damage.…”
Section: Type Of Disease Antigen Diagnostic/prognostic Value Referencesmentioning
confidence: 99%
“…[ 48–50 ] Activated B cells have been observed to secrete various cytokines, including IL‐6, IFN‐γ, TNF‐α, and IL‐10. [ 51,52 ] In contrast, CD4 + T cells that have been activated migrate toward B‐cell follicles and differentiate into Tfh cells, which produce IL‐21 and IFN‐γ. The production of IL‐21 by Tfh cells is crucial in promoting the formation of GCs, as it sustains the expression of B‐cell lymphoma 6 (BCL‐6) and enhances B‐cell activation, CSR, and plasma cell differentiation.…”
Section: Antibodies and Complement In Sle Immunopathogenesismentioning
confidence: 99%
“…In cellular communication, the recognition and interpretation of extracellular signals play a fundamental function in determining cellular behavior ( Hastings et al, 2019 ). Growth factors, cytokines, and hormones emerge as key signaling molecules that elicit cellular responses, regulating cell growth, differentiation, survival, and metabolism ( Miricescu et al, 2021 ; Feng et al, 2022 ). The interaction of these signaling molecules with their corresponding receptors, particularly receptor tyrosine kinases (RTKs), initiates intracellular signaling cascades ( Chen et al, 2017 ; Jiang and Ji, 2019 ).…”
Section: Overview Of Pi3k/akt Signalingmentioning
confidence: 99%
“…CCT3, a major subunit, plays a fundamental role in protein folding, with its gene located on chromosome 1. CCT3 is involved in regulating signaling pathways like STAT3, Wnt, and PI3K-AKT, impacting tumor cell proliferation, differentiation, and apoptosis (Liu W. et al, 2022). The protein CCT3 plays a role in the ferroptosis of lung adenocarcinoma cells.…”
Section: Cct3/akt/slc7a11mentioning
confidence: 99%
“…Immunotherapy is a thriving area and has revolutionized the tumor treatment option (Huang and Zhou 2023;. Over the past two decades, significant research progress has been made, and several types of immunotherapies, including immune checkpoint therapy (ICT), Chimeric Antigen Receptor T-Cell Therapy (CAR-T), and tumor vaccines, have realized clinical translation to benefit many cancer patients (Feng et al 2022). Among them, ICT is the most extensively studied subtype, which reverses the immunosuppressive state of tumor by reinforcing the function of T cells (Ding et al 2022;Zheng et al 2022).…”
Section: Introductionmentioning
confidence: 99%